A Rare Case of Neonatal Hypophosphatasia: A Case Report - Nasim Pouralizadeh; Hassan Boskabadi; Gholamali Mamouri (Mashhad University of Medical Sciences, 2018)
Hypophosphatasia is a rare hereditary disorder of bone metabolism.In this article, we presented the case of a male infant with a soft skull and short, deformed limbs at birth, followed by seizures and respiratory distress during admission in the neonatal intensive care unit (NICU). Prenatal ultrasound showed limb hypoplasia, skull hypomineralization, and polyhydramnios. Seizures occurred on day nine of admission. The neonate was intubated after pneumonia on day 12of birth and died due to the same cause and respiratory failure on day 14. Clinical presentation and low alkaline phosphatase (ALP) confirmed the diagnosis of hypophosphatasia. The disorder covers a spectrum of severe neonatal type with severe hypomineralization to various adult types with osteomalacia and dental problems. Prenatal hypophosphatasia is diagnosed based on the clinical signs, including soft skull, short limbs, breathing difficulty, seizures, respiratory distress, laboratory results (low ALP and high pyridoxal 5-phosphate), and radiographic findings (hypomineralization and metaphyseal dysplasia.